2012
DOI: 10.1002/pts.1974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Dynamic Accumulation Method for Measuring Oxygen Transmission Rate of Packaging against the Steady‐State Method Described by ASTM D3985

Abstract: A new dynamic accumulation method for measuring the oxygen transmission rate (OTR) of packages and packaging films using robust and inexpensive fluorescence oxygen sensing technology has been developed. The method allows for oxygen to transfer through a given area of packaging or sample film and accumulate over time. The test volume incorporates a fluorescence‐based oxygen sensor that does not consume oxygen and therefore does not interfere with the real‐time measurement of oxygen concentration. The new method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 13 publications
(22 reference statements)
0
41
0
Order By: Relevance
“…Nevertheless, PLA/EPO15 had a medium oxygen barrier with OTR that was still (270%) lower than that of neat PLA's. As for PLA that was plasticized with ESO, despite not achieving an entirely impermeable state, all PLA/ESO blends shifted the medium-low oxygen barrier of PLA sheet to medium range (11 to 1000 mL m -2 per day) (Abdellatief and Welt 2012). With at least twice the improvement, the oxygen barrier gradually increased as the ESO loading increased up to 15 wt.%.…”
Section: Barrier Propertiesmentioning
confidence: 94%
“…Nevertheless, PLA/EPO15 had a medium oxygen barrier with OTR that was still (270%) lower than that of neat PLA's. As for PLA that was plasticized with ESO, despite not achieving an entirely impermeable state, all PLA/ESO blends shifted the medium-low oxygen barrier of PLA sheet to medium range (11 to 1000 mL m -2 per day) (Abdellatief and Welt 2012). With at least twice the improvement, the oxygen barrier gradually increased as the ESO loading increased up to 15 wt.%.…”
Section: Barrier Propertiesmentioning
confidence: 94%
“…Oxygen concentration in the DA chamber was measured and recorded periodically during the test using the commecially available oxygen fluorescence sensor (Model 310; Oxysense, Inc). OTR was subsequently calculated as described [16].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…This model can be used to generate accumulation chamber concentration gradients for a film of given permeability P, thickness l , on a chamber of given length, L, with oxygen diffusion coefficient, D, in air, which is similar to oxygen diffusion through nitrogen. The OTR may be calculated from oxygen concentrations predicted at the sensor location within the accumulation chamber via the method described by Welt and Abdellatief, 2012 . When oxygen concentration gradients within the accumulation chamber are insignificant, apparent OTR (OTR apparent ) should be the same as the actual OTR of the film sample used as an input to the model (OTR actual ), where OTRactual=normalPl…”
Section: Model Developmentmentioning
confidence: 99%
“…Prior to this development, dynamic accumulation approaches had been attempted by extracting gas samples from the accumulation chamber for analysis . Recently, performance of florescence‐based dynamic accumulation has been compared with the steady‐state method described by ASTM D3985, and it was found that dynamic accumulation provides similar results to the steady‐state method …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation